2020
DOI: 10.1172/jci142804
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 survival associates with the immunoglobulin response to the SARS-CoV-2 spike receptor binding domain

Abstract: BACKGROUND. Serological assays are of critical importance to investigate correlates of response and protection in coronavirus disease 2019 (COVID-19), to define previous exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in populations, and to verify the development of an adaptive immune response in infected individuals. METHODS. We studied 509 patients confirmed to have COVID-19 from the San Raffaele Hospital of Milan and 480 samples of prepandemic organ donor sera collected in 2010-2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(132 citation statements)
references
References 55 publications
10
119
1
1
Order By: Relevance
“…For this study, we used a LIPS liquid phase immunoassay developed on the basis of our prior expertise. The description of the assay performance and potential caveats [27,28] falls outside the scope of this study and is being published elsewhere [25]. Taken together, our data support the evidence of an efficient humoral response in patients with diabetes, as the prevalence of positivity for the different classes of antibodies to multiple SARS-CoV-2 antigens was superimposable, as for timing and antibody titres, to that of non-diabetic patients and was not influenced by glucose levels.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…For this study, we used a LIPS liquid phase immunoassay developed on the basis of our prior expertise. The description of the assay performance and potential caveats [27,28] falls outside the scope of this study and is being published elsewhere [25]. Taken together, our data support the evidence of an efficient humoral response in patients with diabetes, as the prevalence of positivity for the different classes of antibodies to multiple SARS-CoV-2 antigens was superimposable, as for timing and antibody titres, to that of non-diabetic patients and was not influenced by glucose levels.…”
Section: Discussionsupporting
confidence: 76%
“…Anti-SARS-CoV-2 antibody determination To investigate the presence of anti-SARS-CoV-2 antibodies in patients with COVID-19 pneumonia, we developed a novel assay based on the luciferase immunoprecipitation system (LIPS) format [25]. LIPS is a derivative of the radio-binding assay in which serum antibodies are used to immunoprecipitate radiolabelled antigens in the liquid phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this state of low-grade inflammation in COVID-19 diabetic patients may lead to an increase of the percentage of proinflammatory memory B cells and a decrease of antiinflammatory B-cells, resulting in an early maturation of the antibody response. In that way, Secchi M et al have indicated that SARS-CoV-2 antigens, such as the SARS-CoV-2 spike Receptor Binding Domain, lead to a rapid development of humoral response and superimposable antibody response compared to non-diabetic patients independently of glucose levels (28,36).…”
Section: Pre-existing Overactivation Of Nlrp3 Inflammasome In Diabetementioning
confidence: 99%
“…Specific antibodies to different SARS-CoV2 antigens were tested by a luciferase immunoprecipitation system (LIPS) assay developed in house (13). Serum IgG to Nucleocapsid protein (NP), Receptor binding domain (RBD) and Spike proteins (S1S2) were positive by day 6 after first positive swab and at day 61 ( Figure 2B), reaching levels comparable to those of children who experienced SARS-CoV2 infection (n=3) and higher than the mother ( Figure 2C).…”
Section: Case Presentationmentioning
confidence: 99%